Purchase Intention in Mediating the Effect of Promotion on Purchase Decisions in Tiktok Shop - Santoso, Theo Angelo; Andriyani, Bianka; Algifari, Algifari (Equity: Jurnal Akuntansi, 2025)
This study aims to analyze the influence of promotion, purchase intention, and price perception on purchasing decisions in TikTok Shop. Using a quantitative approach with 132 STIE YKPN Yogyakarta students as the sample, the research utilized multiple regression analysis. The results show that promotion does not have a significant positive effect on purchasing decisions. However, both purchase intention and price perception were found to positively influence purchasing decisions. These findings suggest that while promotions alone may not drive purchases on TikTok Shop, fostering purchase intention and maintaining favorable price perceptions can be key strategies for influencing purchasing decisions. This research highlights the importance of understanding consumer behavior and the mediating role of purchase intention in the context of online shopping platforms like TikTok Shop.